A qualitative study on ICU nurses’ perceptions of palliative care - Mina Omidi; Alireza Abdi; Maryam Rezaei (BMC Nursing)
Abstract Introduction Providing palliative care is one of the most essential responsibilities of nurses toward patients and their families. To fulfill this role effectively, nurses require specific skills to understand patients better and gain their trust. Given the necessity of delivering palliative care and the limited studies available in Intensive Care Units (ICUs), this study aimed to explore the perceptions of nurses working in ICUs in Kermanshah Province. Methods This qualitative study employed a descriptive phenomenological approach. Data were collected through purposive sampling via semi-structured interviews with 13 ICU nurses employed at hospitals affiliated with Kermanshah University of Medical Sciences. The interviews were recorded, transcribed verbatim, and analyzed using the Collaizi method, with data management conducted through MAXQDA-10 software. Results Of the 13 participating nurses, 9 were female and 4 were male, with a mean age and work experience of 29.69, and 6.54 years, respectively. Four main themes and nine sub-themes emerged from the qualitative analysis. The primary themes included: “Understanding the meaning and concept of palliative care,” “Nurses’ perception of the types of palliative care,” “Strengthening the foundations of palliative care for ICU nurses,” and " Factors contributing to palliative care”. Conclusion The findings highlighted several critical factors necessary for the effective provision of palliative care in ICUs, including nurses’ understanding, patience, required knowledge, and a strong work ethic. These factors collectively enhance the quality of palliative care provided to patients. Given the pivotal role of palliative care in improving nursing care for critically ill patients, it is recommended that further qualitative studies be conducted to deepen nurses’ understanding of palliative care in ICUs.